Inkulturasi Budaya Lokal dalam Liturgi Gereja: Makna Torok Tae sebagai Ungkapan Syukur Iman Umat Manggarai - Karolina Suwul; Intansakti Pius X (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Church in indonesia now plays an increasingly broad role in society, but also faces various complex challenges. These challenges come not only from outside, such as discrimination and social pressure, but also from within; such as limited resources and a reluctance to change. Therefore, the Church needs to understand these various issues in order to formulate ministry strategies that are relevant, contextual, and able to addres the needs of a diverse society. The Church is called to be a forum for the brotherhood of God’s people from various cultural backgrounds, while also bearing witness that unity in diversity is a tangible manifestation of God’s love in the world. However, cultural diversity can also create tension if not managed wisely. The inculturation of local cultures, such as Torok in Manggarai culture, has profound meaning. Torok is not merely a series of literary words, but has a profound meaning that reflects the identity of the Manggarai people in their relationship with themselves, others, nature, and God Himself as creator. As a poetic prayer, Torok serves as an expression of the totality of human life and a means to cultivate the values of brotherhood. The Church does not intend to implement rigid uniformity in matters that do not concern the core of the faith or the welfare of the faithful. On the contrary, the Church respects and strives to preserve the cultural riches that are characteristic of various tribes and nations.